2014
DOI: 10.1016/j.urology.2014.02.028
|View full text |Cite
|
Sign up to set email alerts
|

A Population-based Analysis of Contemporary Rates of Reoperation for Penile Prosthesis Procedures

Abstract: OBJECTIVES To perform a population based comparison of inflatable versus semi-rigid penile prostheses to determine contemporary rates of re-operation and identify factors impacting the type of prosthetic implanted. METHODS Patient level discharge data and revisit files from the Agency for Healthcare Research and Quality for semi-rigid and inflatable prosthesis procedures performed for erectile dysfunction from 2006-2009 in the state of California were examined. Regression analysis was performed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 10 publications
0
21
0
3
Order By: Relevance
“…Penile implant infection leads to increased patient morbidity, patient hospital re‐admission, prolonged surgery‐related hospital stay, prolonged use of broad spectrum antibiotics, and implant removal . Grewal et al surveyed patients discharge and re‐visit data in a contemporary series of penile implant surgeries and found that infectious complications were the most common reason for reoperation. Whilst Lledó‐García et al reported high patient and partner satisfaction after both primary and replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Penile implant infection leads to increased patient morbidity, patient hospital re‐admission, prolonged surgery‐related hospital stay, prolonged use of broad spectrum antibiotics, and implant removal . Grewal et al surveyed patients discharge and re‐visit data in a contemporary series of penile implant surgeries and found that infectious complications were the most common reason for reoperation. Whilst Lledó‐García et al reported high patient and partner satisfaction after both primary and replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Caucasian race was independently associated with receipt of inflatable penile prosthesis, highlighting racial disparities in the surgical management of ED. Racial variation in the selection of penile prosthetic surgery was also described recently using a California administrative data set by Grewal et al in which the authors demonstrated that African-American men were more likely to receive a semi-rigid implant [20]. Lower socioeco-nomic status may account for selection of less expensive, and thus, semi-rigid implant; however, these findings highlight disparities in care warranting further investigation.…”
Section: Discussionmentioning
confidence: 70%
“…Grewal et al. [20] similarly noted that ethnicity and Medicaid or self‐pay insurance status were significant predictors for receiving a semirigid prosthesis. The unequal utilization of surgical techniques according to ethnicity has also been previously reported; Yu et al.…”
Section: Discussionmentioning
confidence: 99%